Interactive children, communicative teaching : ICT and classroom teaching - Cook, Deirdre; Finlayson, Helen (Buckingham : Open University Press, 1999)
This book is about: ICT learning at home and at school; Taking play seriously; ICT as a learning tool; Managing learning; ...
Keywords: Education; Computer; Telecommunication systems; Information technology; Computer-assisted instruction; Telecommunication in education